INTRADIALYTIC EXERCISE ON BLOOD PRESSURE IN CHRONIC KIDNEY FAILURE PATIENTS UNDERGOING HEMODIALYSA - Hapipah; Istianah, Istianah; Cahyati, Nurul (Jurnal Keperawatan Widya Gantari Indonesia, 2024)
Chronic kidney failure is a disorder in which the kidneys are unable to filter blood. Patients with stage 5 chronic kidney failure have two options for overcoming the problem: hemodialysis or kidney transplantation in the aim of maintaining their life. The 5-hour hemodialysis process often involves physical stress, resulting in blood pressure fluctuations. The purpose of this study was to assess the effect of intradialytic exercise on blood pressure in chronic kidney failure patients receiving hemodialysis at Mataram City Regional General Hospital. In this study, 18 persons were sampled using the purposive sampling technique. This is a pre-experimental quantitative study with a one-group pretest-posttest design. The Paired T-test and the Wilcoxon rank sum test were employed in this study. Bivariate analysis indicates that intradialytic exercise has an effect on systolic and diastolic blood pressure in chronic kidney failure patients receiving hemodialysis at Mataram City Regional General Hospital, with p values of 0.001 (<0.05) for systole and 0.004 (<0.05) for diastole. The findings of this study indicate that intradialytic exercise is an alternative nursing intervention for overcoming blood pressure fluctuations in patients with chronic kidney failure following hemodialysis therapy.